Combining ability and gene action for resistance to Fusarium ear rot in tropical maize hybrids - Ayesiga, Stella Bigirwa; Rubaihayo, Patrick; Sempiira, John Bosco; Adjei, Emmanuel Amponsah; Dramadri, Isaac Onziga; Oloka, Bonny Michael; Sserumaga, Julius Pyton (Frontiers in Plant Science, 2025)
A comprehensive understanding of the genetics of resistance is essential for developing an effective breeding strategy to create germplasm resistant to Fusarium Ear Rot. This study aimed to determine the general combining ability (GCA), specific combining ability (SCA), and heritability of resistance to infection by Fusarium verticillioides in tropical maize. Using the North Carolina II mating design, six inbred lines as females and seven as males were crossed to produce 42 hybrids, which were evaluated across five environments using artificial inoculation. At harvest, the hybrids were scored for Fusarium Ear Rot (FER) infection using a 1-9 severity scale. Significant GCA effects for the parents and SCA effects for the hybrids were observed. The narrow-sense heritability estimate was 0.22, while the broad-sense heritability was 0.73, and the additive genetic effects, as represented by GCA (m+f), were more significant than non-additive effects. The inbred parents JPS25-13, JPS26-125, JPS26-86, JPS25-11, JPS25-5, JPS25-7, and JPS25-9 were identified as the best general combiners for FER resistance. These lines, with favorable general combining ability effects for resistance to Fusarium verticillioides, are strong candidates for breeding resistant varieties.